Resident perceptions of the impacts of P2P accommodation: Implications for neighbourhoods - Stergiou, Dimitrios P.; Farmaki, Anna (My University, 2020)
Although a research base is beginning to emerge in relation to the peer-to-peer accommodation phenomenon, the voices of residents are seldom heard in this scholarly literature. This study uses Social Exchange Theory to examine resident perceptions regarding the impact of P2P accommodation growth, and specifically Airbnb, on their neighbourhood. Fifty-one semi-structured interviews were employed to illuminate understanding of how resident perceptions are formed in relation to the exchange relationship with Airbnb guests. Findings reveal a dominance of negative perceptions of socio-economic and environmental impacts. The study also contributes a typology of residents, based on their perceptions and behaviour towards associated impacts, which may guide policymakers and practitioners towards the adoption of an anthropocentric approach on P2P accommodation. The study concludes with a discussion of theoretical and practical implications.
Keywords: Airbnb; Impacts; Neighbourhoods; P2P accommodation; Social exchange theory